Implementasi Pembelajaran Kemuhammadiyahan bagi Peserta Didik Autis di Madrasah Aliyah Muhammadiyah 1 Kota Malang - Siti Julaiha; Sunarto; Zulfikar Yusuf (Mu'allim, 2024)
Students with autism, with all their strengths and weaknesses compared to regular students, undoubtedly imply differences in treatment, especially in the context of teaching and learning in the classroom. The equalization of learning implementation in various cases has resulted in non-contextual learning implementation. Based on this, the formulation of the research problem is how Muhammadiyah learning occurs between educators and students with autism at MA Muhammadiyah 1 Kota Malang, specifically focusing on the aspects of planning, implementation, and evaluation of learning. Therefore, the aim of this research is to describe Muhammadiyah learning for students with autism at MA Muhammadiyah 1 Kota Malang, specifically focusing on the aspects of planning, implementation, and evaluation of learning. This research uses a qualitative approach of a case study type with the determination of research informants determined through purposive sampling techniques. Data collection is carried out using observation techniques, interviews, and documentation. Meanwhile, data analysis uses the Miles and Huberman analysis flow, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that MA Muhammadiyah 1 Kota Malang, in the application of the planning aspect, has not yet implemented the things outlined in the ISMUBA Curriculum. The implementation aspect shows that constraints still occur in closing activities, and in terms of the evaluation aspect of learning, it is evident that based on conditions appropriate to the abilities of autistic students, assessments are carried out.